Pengembangan Media Video Pembelajaran Berbasis Explainer pada Mata Pelajaran Informatika Materi Jaringan Komputer dan Internet di SMA - Heru Paituh Rahmat; Darmansyah; Septriyan Anugrah; Alkadri Masnur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop an explainer-based learning video for the Informatics subject on the topic of Computer Networks and the Internet in senior high school and to determine its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects included media experts, material experts, an Informatics teacher, and tenth-grade students of SMA Negeri 1 Lengayang. Data were collected through observations, interviews, validation questionnaires, practicality questionnaires, and learning outcome tests. The product developed was an explainer-based learning video created using the CapCut application. The development process began with a needs analysis that identified students' difficulties in understanding Computer Networks and Internet concepts due to the limited use of interactive learning media. The video was designed by integrating visual illustrations, animations, text, and narration to facilitate students' understanding of abstract concepts. The results showed that the developed media achieved a very valid category, with a material validation score of 4.84. Furthermore, the practicality and effectiveness tests indicated that the learning video was highly practical and effective for classroom use. The findings suggest that the explainer-based learning video is suitable for supporting the teaching and learning process and can help improve students’ understanding of Computer Networks and Internet material in Informatics learning at the senior high school level.